The symbolic value of wine, moderating and mediating factors and their relationship to consumer purchase intention. Issue 2 (17th September 2021) - De Toni, Deonir; Pompermayer, Rogério; Lazzari, Fernanda; Milan, Gabriel Sperandio
Abstract : Purpose: The symbolic value of wine is a relevant research topic and raises the interest in studies in both the enological and market areas. In this context, this study aims to understand the role of the symbolic value of wine and its relationship to the product purchase intention. Design/methodology/approach: The study is based on a survey of 269 wine consumers from Brazil. The basic theoretical framework includes three latent constructs (symbolic value, consumer attitude and product-norm experience) and three moderators (consumer involvement, willingness to pay and consumer preference). Relations between these are analyzed using the confirmatory factor analysis (CFA) and the moderated mediation analyses using Haye's process. Findings: This research identified that the symbolic value is totally mediated by consumers' attitudes and product-norm experiences. However, such a relationship occurs directly for consumers with higher involvement with the product, higher willingness to pay, and who assume that wine is their preferred alcoholic beverage. Originality/value: One of the contributions is to emphasize the symbolic value of wine and highlight how the relationship with different factors can interfere and explain consumer purchase intention and can influence the strategies, actions and investments of companies in the sector.